2023
DOI: 10.1021/acssuschemeng.3c02052
|View full text |Cite
|
Sign up to set email alerts
|

Circular Economy Electrochemistry: Recycling Old Mixed Material Additively Manufactured Sensors into New Electroanalytical Sensing Platforms

Abstract: Recycling used mixed material additively manufactured electroanalytical sensors into new 3D-printing filaments (both conductive and non-conductive) for the production of new sensors is reported herein. Additively manufactured (3D-printed) sensing platforms were transformed into a non-conductive filament for fused filament fabrication through four different methodologies (granulation, ball-milling, solvent mixing, and thermal mixing) with thermal mixing producing the best quality filament, as evidenced by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…The resistance continued to decrease with increasing amounts of MWCNT; however, the printability of the filament was greatly diminished above 40% MWCNT, with the filament becoming brittle. The MWCNT with CB (10 wt%/15 wt%, 40:60% ratio of MWCNT to CB) filament was therefore chosen and then produced using the same thermal mixing techniques as outlined previously [ 27 , 29 , 33 , 34 ] and represented in Fig. 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance continued to decrease with increasing amounts of MWCNT; however, the printability of the filament was greatly diminished above 40% MWCNT, with the filament becoming brittle. The MWCNT with CB (10 wt%/15 wt%, 40:60% ratio of MWCNT to CB) filament was therefore chosen and then produced using the same thermal mixing techniques as outlined previously [ 27 , 29 , 33 , 34 ] and represented in Fig. 1 A.…”
Section: Resultsmentioning
confidence: 99%
“…This facile production would be a huge step toward commercialisation of additive manufactured electrochemical biosensors. This print was also shown to be recyclable, 64 which indicates another area of benefit for additive manufacturing electrochemistry over more established techniques such as screen-printing. The sensing of glucose is a key biosensor target and has continued to be the focus of immense research activity where continuous glucose monitoring can reduce the risks of diabetes induced diseases allowing the diabetics to sustain a healthy lifestyle while precluding the costly and lethal late-stage diabetic complications.…”
Section: Additive Manufacturing Biosensors Using Commercially Availab...mentioning
confidence: 96%
“…53 Recently, researchers have begun to design and produce their own conductive filament utilising different loadings and nanomaterials compared to the commercially available options. 54–56 Silva et al 52 took this approach and have reported the design of a fully AM microfluidic platform coupled with a paper-based distribution channel for the sensing of carbendazim within in honey samples. As shown within Fig.…”
Section: Electroanalytical Based Sensors For Carbendazimmentioning
confidence: 99%